2003
DOI: 10.1007/s00244-002-1267-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol and Nonylphenol Ethoxylates in Fish, Sediment, and Water from the Kalamazoo River, Michigan

Abstract: Abstract.A survey measuring concentrations of nonylphenol (NP) and its ethoxylates (NPEs) in fish was performed in the Kalamazoo River, Michigan, USA, in 1999. Of 183 fish analyzed, 59% had no detectable NP or NPE. Detected concentrations were reported to range from 3.3 (limit of detection) to 29.1 ng NP/g wet weight. To further explore the means of exposure of NP and NPE in the fish, concentrations of NP and its mono-through tri-ethoxylates (NPE 1-3 ) were measured in fish, sediment, and water collected near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…While several studies have examined the residues of 4-NP and NPEOs with short EO units (s < 6) in fish (3,10,13,14,16), there is little documenting the existence of NPEOs with more than five units in biota, and there are no reports of the occurrence of NPEOs in marine biota. As shown in the Supporting Information, each NPEO with 3 < s <16 was detected in all biota samples, which provided the first report on the occurrence of NPEOs with s > 5 in marine biota.…”
Section: Ddts 4-np and Npeos Concentrations In Marine Biota From Bomentioning
confidence: 99%
“…While several studies have examined the residues of 4-NP and NPEOs with short EO units (s < 6) in fish (3,10,13,14,16), there is little documenting the existence of NPEOs with more than five units in biota, and there are no reports of the occurrence of NPEOs in marine biota. As shown in the Supporting Information, each NPEO with 3 < s <16 was detected in all biota samples, which provided the first report on the occurrence of NPEOs with s > 5 in marine biota.…”
Section: Ddts 4-np and Npeos Concentrations In Marine Biota From Bomentioning
confidence: 99%
“…These include the induction of estrogenresponsive genes in males such as vitellogenins (vtgs) and choriogenins that are involved in normal female reproduction (Allen et al 1999, Arukwe et al 2001, Kannan et al 2003, impaired gonadal development (Lin & Janz 2006), altered steroidogenesis (Harris et al 2001), and intersex (Gray et al 1997, Metcalfe et al 2001, Schwaiger et al 2002, Seki et al 2003. These conditions have been induced in fish in controlled laboratory studies and have also been seen in wild fish found in the vicinity of sewage outflows (Allen et al 1999, Jobling et al 2002, Legler et al 2002, Pettersson et al 2005 where the main contaminants include NP.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of NPEOs and intermediates in water and sediment in the United States, Europe, and Japan has been well documented (Naylor et al 1996;Kannan et al, 2003;Ahel et al 1994;Di Corcia et al 2000;Maruyama et al 2000, Thiele et al 1997. Recently, several studies have examined the residues of 4-NP and NPEOs with short EO units (n < 6) in fish (Rice et al 2003;Tsuda et al 2000;Keith et al 2001;Lye et al 1999;Ferrara et al 2001;Kannan et al, 2003).…”
mentioning
confidence: 99%
“…Recently, several studies have examined the residues of 4-NP and NPEOs with short EO units (n < 6) in fish (Rice et al 2003;Tsuda et al 2000;Keith et al 2001;Lye et al 1999;Ferrara et al 2001;Kannan et al, 2003). To date, there is no documented evidence of the existence of NPEOs with more than 5 units in fish.…”
mentioning
confidence: 99%